Comparative analysis of noncoding sequences of orthologous bovine and human gene pairs - Miziara, Melissa Nunes [UNESP]; Riggs, Penny K.; Amaral, M. Elisabete J. [UNESP] (My University, 2004)
Genomic sequence comparison across species has enabled the elucidation of important coding and regulatory sequences encoded within DNA. Of particular interest are the noncoding regulatory sequences, which influence gene transcriptional and posttranscriptional processes. A phylogenetic footprinting strategy was employed to identify noncoding conservation patterns of 39 human and bovine orthologous genes. Seventy-three conserved noncoding sequences were identified that shared greater than 70% identity over at least 100 bp. Thirteen of these conserved sequences were also identified in the mouse genome. Evolutionary conservation of noncoding sequences across diverse species may have functional significance, and these conserved sequences may be good candidates for regulatory elements.
Keywords: Bovine; Comparative analysis; DNA sequences; Genes; Orthologous; comparative study; conference paper; DNA determination; DNA sequence; gene identification; gene sequence; genetic transcription; genome; mouse strain; nucleotide sequence; statistical significance; unindexed sequence; 3' Untranslated Regions; 5' Untranslated Regions; Animals; Base Sequence; Cattle; Conserved Sequence; Evolution, Molecular; Humans; Mice; Molecular Sequence Data; Sequence Alignment; Sequence Analysis, DNA; Bovinae